Multi-omics analysis reveals the alleviating effect of oxidation remediation on tobacco quinclorac stress - Zhang, Binghui; Yang, Ting; Cheng, Chenliang; Li, Tong; Zhang, Ni; Wang, Fei; Chen, Wencan; Zhong, Zhiping; Liu, Zhaoxiang; Gu, Gang; Lin, Xiangmin; Xie, Xiaofang (Frontiers in Microbiology, 2025)
The extensive use of the herbicide quinclorac has led to significant residues in agricultural soil, posing adverse effects on crop safety and high-quality production. In this study, using the tobacco variety CB-1 as material, we found that oxidizing agent K2S2O8 can significantly reduce quinclorac-induced phytotoxicity symptoms in tobacco. Furthermore, we integrated biochemical methods, metagenomics, metabolomics, and transcriptomics to investigate the effects of K2S2O8 on both quinclorac-contaminated soil and tobacco plants. Soil physicochemical properties analysis showed that the incorporation of K2S2O8-based remediation significantly mitigated the negative effects of quinclorac and largely restored the soil properties affected by quinclorac stress. Metagenomic analysis found that quinclorac significantly reduced soil species diversity, while K2S2O8-based remediation soil exhibited higher richness of microbial communities, with increased abundance of Sphingomonas and Bradyrhizobium, and decreased abundance of Alphaproteobacteria. Differential gene expression analysis showed significant up-regulation and down-regulation of genes under C10H5Cl2NO2 stress, which was partially mitigated by K2S2O8 treatment. Gene Ontology (GO) enrichment analysis indicated that these genes were mainly involved in cellular processes, metabolic pathways, and biological regulation. Metabolomic analysis further confirmed significant changes in metabolite profiles, with K2S2O8 treatment restoring many metabolites to near control levels. Integrated metabolomic-transcriptomic analysis revealed enrichment of differentially expressed genes (DEGs) and metabolites in six key pathways: (1) lysine degradation, (2) stilbenoid diarylheptanoid and gingerol biosynthesis, (3) arginine and proline metabolism, (4) phenylalanine biosynthesis, (5) tyrosine metabolism, and (6) flavonoid biosynthesis. Additionally, the levels of 4-hydroxyphenylacetylglutamic and 5-aminovaleric acid were down-regulated, along with the expression of genes associated with these metabolites, when quinclorac residual soil was treated by K₂SO8. The results of this study provide a theoretical basis for the remediation of pesticide residue soil in rice tobacco rotation areas, offering valuable insights for sustainable agricultural practices.